Prevention and Management of Sexual Violence in Higher Education Institutions from the Perspective of Maqāṣid al-Sharī‘ah: An analysis of Permendikbudristek No. 55 of 2024 - Siti Nur Riani; Andri Gunawan; Siti Marhamah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Sexual violence in higher education institutions has become an increasingly critical issue due to its far-reaching impacts on human rights, mental health, personal safety, and the continuity of victims’ education. This phenomenon not only disrupts the learning process and the implementation of the tridharma of higher education, but also creates an unsafe and unconducive academic environment that hinders the development of students’ and academics’ potential. In response to the complexity of various forms of violence occurring on university campuses, the Indonesian government enacted the Minister of Education, Culture, Research, and Technology Regulation No. 55 of 2024 concerning the Prevention and Management of Violence in Higher Education Institutions. This study aims to analyze the substance of this regulation from the perspective of maqāṣid al-sharī‘ah, particularly regarding the protection of human rights and dignity. The research employs a normative legal method using both statutory and conceptual approaches through library research. Data were collected from legislation, Islamic legal literature, books, and relevant scholarly publications. The findings indicate that Regulation No. 55 of 2024 is strongly aligned with the fundamental objectives of Islamic law, namely the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and human dignity (ḥifẓ al-‘irḍ). The regulation also adopts a victim-centered approach through prevention, reporting mechanisms, assistance, recovery services, and the establishment of Violence Prevention and Management Task Forces within higher education institutions. Therefore, the regulation not only possesses legitimacy within the national legal system but also accords with the principles of public welfare (maṣlaḥah) and the prevention of harm (daf‘ al-mafāsid) within the framework of maqāṣid al-sharī‘ah.